2017
DOI: 10.1080/14763141.2016.1252790
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activity in sprinting: a review

Abstract: The use of electromyography (EMG) is widely recognised as a valuable tool for enhancing the understanding of performance drivers and potential injury risk in sprinting. The timings of muscle activations relative to running gait cycle phases and the technology used to obtain muscle activation data during sprinting are of particular interest to scientists and coaches. This review examined the main muscles being analysed by surface EMG (sEMG), their activations and timing, and the technologies used to gather sEMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 31 publications
3
50
0
2
Order By: Relevance
“…The literature concerning sEMG applications in sports is very extensive and focused on physiology ( 191 , 192 ) training, prevention of injury, and recovery after injury (in particular the anterior cruciate ligament injury ( 193 ). Many sports have been investigated, in particular golf ( 194 ), jumping ( 195 ), cycling ( 196 ), sprinting ( 197 ), volleyball ( 198 ), but also strength training ( 199 , 200 ), back pain in rowers ( 201 ), patellofemoral pain ( 170 , 202 ), and aging ( 59 , 203 ). The distribution of muscle fiber conduction velocity, related to fiber diameter, may provide insight in muscle structure.…”
Section: Surface Emg Applicationsmentioning
confidence: 99%
“…The literature concerning sEMG applications in sports is very extensive and focused on physiology ( 191 , 192 ) training, prevention of injury, and recovery after injury (in particular the anterior cruciate ligament injury ( 193 ). Many sports have been investigated, in particular golf ( 194 ), jumping ( 195 ), cycling ( 196 ), sprinting ( 197 ), volleyball ( 198 ), but also strength training ( 199 , 200 ), back pain in rowers ( 201 ), patellofemoral pain ( 170 , 202 ), and aging ( 59 , 203 ). The distribution of muscle fiber conduction velocity, related to fiber diameter, may provide insight in muscle structure.…”
Section: Surface Emg Applicationsmentioning
confidence: 99%
“…The full sprint gait cycle is typically divided in to two discrete phases: the closed kinetic chain 'stance', an epoch definable as equivalent to ground contact time, and the open kinetic chain 'swing'; representing the time the foot is airborne (Higashihara et al, 2013). Further sub-divisions are often present, highlighting the changing demands of the full cycle (Howard et al, 2018). (see Fig.…”
Section: The Dynamic Demands Of High Velocity Runningmentioning
confidence: 99%
“…In order to maximize transfer of strength to performance, closed-chain RT exercises involving similar movement patterns to sporting performance are recommended (Seitz et al, 2014;Burnie et al, 2017). As such, knee extensors are a common focus of RT owing to their involvement in athletic movement patterns (e.g., sprinting and jumping) (Jacobs et al, 1996;Simsek et al, 2016;Howard et al, 2017). Commonly, the efficacy of such RT is commonly measured by 1 maximal repetition (1RM) tests in strength and conditioning settings (Levinger et al, 2009), providing an indication of any change observed in muscle function.…”
Section: Introductionmentioning
confidence: 99%